2019
DOI: 10.1021/acsapm.9b00830
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Linear Segmented Polyurethanes Simultaneously Having Shape Recovery and Self-Healing Properties

Abstract: Double-decker silsesquioxane (DDSQ) and hindered urea bonds were simultaneously introduced into the main chains of linear segmented polyurethane (PU) to synthesize organic–inorganic linear segmented poly­(urea urethanes) (PUUs). The organic–inorganic PUUs were microphase-separated, and the POSS cages were aggregated into the microdomains with the size of 10–20 nm. The organic–inorganic PUUs had the improved thermomechanical properties in comparison to those of the control PU. Notably, the strong physical cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…Furthermore, poly­(hindered urea) (PHU) networks are degradable and less costly when synthesized by a facile step-growth polymerization of various polyamines including multifunctional bulky amines with polyisocyanates. Several reports have described the development of cross-linked poly­(urea-urethane) and PHU vitrimers to achieve thermal malleability and recyclability. Moreover, reports have explored the use of silsesquioxane, bisphenol S, and a three-arm star isocyanate , that react with a difunctional hindered amine ( N , N -di­( tert -butyl)­ethylenediamine) and the synthesis of a methacrylate bearing t -butylamine pendants . Despite these advances, the development of a robust approach is required for the fabrication of PHU networks with enhanced mechanical properties as well as excellent self-healability and processability.…”
mentioning
confidence: 99%
“…Furthermore, poly­(hindered urea) (PHU) networks are degradable and less costly when synthesized by a facile step-growth polymerization of various polyamines including multifunctional bulky amines with polyisocyanates. Several reports have described the development of cross-linked poly­(urea-urethane) and PHU vitrimers to achieve thermal malleability and recyclability. Moreover, reports have explored the use of silsesquioxane, bisphenol S, and a three-arm star isocyanate , that react with a difunctional hindered amine ( N , N -di­( tert -butyl)­ethylenediamine) and the synthesis of a methacrylate bearing t -butylamine pendants . Despite these advances, the development of a robust approach is required for the fabrication of PHU networks with enhanced mechanical properties as well as excellent self-healability and processability.…”
mentioning
confidence: 99%
“…We observed that as-made hydrogels exhibited initial tensile moduli of ∼815 kPa, which is among the strongest supramolecular hydrogels with healing ability as compared with other recently reported self-healing materials with comparable healing times (Table S1). We found that upon severing the hydrogels and healing for 24 h, the initial tensile modulus was similar at 785 ± 40 kPa.…”
Section: Resultsmentioning
confidence: 84%
“…[ 115 ] Rowan and coworkers studied the impact of steric hinderance of N ‐alkyl substituents and network connectivity in poly(alkylurea‐urethane) dynamic network films to guide the design and properties of dynamic hindered urea networks. [ 116 ] Further, the use of t‐butylamino group‐based bulky urea bond as N , N ‐di‐(tert‐butyl)ethylenediamine (a difunctional hindered amine) has been explored to fabricate various shape‐memory PHU networks containing bisphenol S, [ 117 ] silsesquioxane, [ 118 ] triisocyanate, [ 119 ] azidine, [ 120 ] and others. [ 121 ]…”
Section: Incororation Of Dynamic Covalent Chemistriesmentioning
confidence: 99%